Արևելյան պոեզիայի առանձնահատկությունների դրսևորումը Յ. Վ. Գյոթեի «Արևմտա–Արևելյան դիվանում» - Մելքոնյան, Հասմիկ («Զանգակ - 97»)
In 1819 was published the "Western-Eastern Di v a n " of Goethe.The authorpresents the peculiarity of the west and east lecture and especially poetry in it. The eastern traditions and customs are mixed, interlaced with westem in "Divan", which crcatcs the west-eastem rieh colour. Thanks to Goethes individuality and ex d u si vc talent, he could keep the peculiarities of eastern poetry, the inner life of eastern heros, but in the same time he could save his own individuality.
Keywords: Բանահյուսություն